2017
DOI: 10.5649/jjphcs.43.592
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Pharmaceutical Properties and Economics of Ethical and Rx-OTC-switch Anti-allergy Ophthalmic Solutions

Abstract: To provide appropriate information concerning ethical or Rx-OTC-switch drugs containing the same ingredients by pharmacists, it is necessary to understand the properties of both. In this study, pharmaceutical properties and economics were compared between ethical and Rx-OTC-switch anti-allergy ophthalmic solutions containing tranilast, pemirolast, or acitazanolast. Regarding 14 ethical and 3 Rx-OTC-switch products, the squeeze force, drop weight, pH, specific gravity, and total number of drops were measured. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The hardness and squeeze characteristics of each eye drop container are important not only in terms of ease of use, but also in terms of economy. Murakami et al reported that the shape of the eye drop container, the material of the main body, and the hardness of the container can influence the squeeze characteristics (15). Similarly, the squeeze force was reported to be affected by the material and hardness of the container, whereas the drop volume is affected by the surface tension of the eye drops and the opening diameter of the nozzle tip of the container (16).…”
Section: Discussionmentioning
confidence: 99%
“…The hardness and squeeze characteristics of each eye drop container are important not only in terms of ease of use, but also in terms of economy. Murakami et al reported that the shape of the eye drop container, the material of the main body, and the hardness of the container can influence the squeeze characteristics (15). Similarly, the squeeze force was reported to be affected by the material and hardness of the container, whereas the drop volume is affected by the surface tension of the eye drops and the opening diameter of the nozzle tip of the container (16).…”
Section: Discussionmentioning
confidence: 99%